Al Kufa: the Origin and Name, its Social & Political Life - Alfatlawi, Ali; AlQassi, Nahidh (Al-Adab Journal, 2023)
Al Kufa is one of the Islamic cities that enjoyed a special historical status, since it has a spiritual and civil presence in the history of the Islamic nation and the religious non-Islamic sectors. Originally speaking, the city was built on top of the remains of a Parthian city belongs to Vologases I (51-78AC). It is mention in the Bible 1st testament by the name of Akwala or Agola. Accordingly, historically, it is a Syriac city; while spiritually and religiously it is known as the home of the prophet Noah (Peace Be Upon Him) and the very place of which the holy fire of Noah evolved.The term ‘Kufa’ comes from the term’s meaning and its linguistic references. Al Kufa in Lexical dictionaries is an utterance refers to the land that has red sand or round sand, according to linguists it is the sand that is mixed with gravel. There is an opinion related to fact that when the Islamic leader Saad Bin Abi Waqas decided to build Al Kufa he said to his soldiers “Takawafo fi Hadha Al Makan” meaning, Gather in this spot of land.The establishment of the city of Al Kufa was military necessity, as it provided logistic support to the Islamic army that was the conqueror and the liberator of the lands outside the boarders of Arabic peninsula. That is due to the importance of the geographical location of the area of Kufa, which created the need to military camp and a location that may provide a strategic depth for the Islamic faith supplement to spread more among other nations. That is in addition to what the area enjoys of the geographical features of being at the edge of the desert and it provided the healthy conditions for the life of Arabs and their animals.For all the above reasons, Arabs chose Al Kufa to be the second Islamic city that were established after Al Basrah in 17H. / 638-639AC. Kufic society extended largely in the political life of Muslims. The city of Al Kufa is known for being political stubborn, they were led by Imam Ali bin Abi Talib (Peace be Upon Him) (35-40H./ 656-660AC). He managed to spread the spirit of justice and equality among Arabs and those who lived in the city of non-Arabs and of other religious beliefs. He even commanded one of his employees in Kufa saying: “Beware not to hit a Muslim or a Jewish or a Christian, asking for Kharaj money [Islamic tax] or selling a working animal for tax, we are commanded to forgive and tolerate”, hence the Jewish and Christian with their fellow Muslims a share of religious tolerance and charity from the Righteous Caliphs (May Allah praise them)